Analysis of Reverse-Bias Leakage Current Mechanisms in Metal/GaN Schottky Diodes - P. Pipinys; V. Lapeika (Advances in Condensed Matter Physics)
Temperature-dependent reverse-bias current-voltage characteristics obtained by other researchers for Schottky diodes fabricated on GaN are reinterpreted in terms of phonon-assisted tunneling (PhAT) model. Temperature dependence of reverse-bias leakage current is shown could be caused by the temperature dependence of electron tunneling rate from traps in the metal-semiconductor interface to the conduction band of semiconductor. A good fit of experimental data with the theory is received in a wide temperature range (from 80 K to 500 K) using for calculation the effective mass of 0.222 me. and for the phonon energy the value of 70 meV. The temperature and bias voltages dependences of an apparent barrier height (activation energy) are also explicable in the framework of the PhAT model.